CO2 emission thresholds for inclusive human development in Sub-Saharan Africa - Simplice Asongu (African Governance and Development Institute (AGDI), 2018)
We provide policy-relevant critical masses beyond which, increasing CO2 emissions negatively affects inclusive human development. This study examines how increasing CO2 emissions affects inclusive human development in 44 Sub-Saharan African countries for the period 2000-2012. The empirical evidence is based on Fixed Effects and Tobit regressions. In order to increase the policy relevance of this study, the dataset is decomposed into fundamental characteristics of inclusive development and environmental degradation based on income levels (Low income versus (vs.) Middle income); legal origins (English Common law vs. French Civil law); religious domination (Christianity vs. Islam); openness to sea (Landlocked vs. Coastal); resource-wealth (Oil-rich vs. Oil-poor) and political stability (Stable vs. Unstable). All computed thresholds are within policy range. Hence, above these thresholds, CO2 emissions negatively affect inclusive human development.
Keywords: C52; O38; O40; O55; P37; 330; CO2 emissions; Economic development; Africa